2017
DOI: 10.1536/ihj.16-605
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Inflation Technique Using a Scoring Balloon for Severe Calcified Lesion

Abstract: SummaryPercutaneous coronary intervention for the treatment of a severe calcified lesion is still one of the most technically challenging areas of interventional cardiology. Calcified lesions are a cause of stent underexpansion, which significantly increases the subsequent risks of in-stent restenosis and thrombosis, even when drug-eluting stents are used. In this report, we describe the usefulness of prolonged inflations using a scoring balloon catheter (Scoreflex) for severe calcified lesions. Prolonged infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…[46] Otsuka et al reported a case series where prolonged inflation of the Scoreflex balloon allowed adequate dilation of severe calcified plaques as shown by the ‘creep phenomenon’, whereby prolonged inflation of the balloon produces a distortion force capable of expanding a resistant calcified lesion. [47] Scoring balloons have been considered by cardiologists as an alternative to cutting balloons and, in recent years, have been preferred because of major flexibility and deliverability, although no specific randomised control trials are reported in the literature.…”
Section: Percutaneous Coronary Intervention Of Complex Calcified Coromentioning
confidence: 99%
“…[46] Otsuka et al reported a case series where prolonged inflation of the Scoreflex balloon allowed adequate dilation of severe calcified plaques as shown by the ‘creep phenomenon’, whereby prolonged inflation of the balloon produces a distortion force capable of expanding a resistant calcified lesion. [47] Scoring balloons have been considered by cardiologists as an alternative to cutting balloons and, in recent years, have been preferred because of major flexibility and deliverability, although no specific randomised control trials are reported in the literature.…”
Section: Percutaneous Coronary Intervention Of Complex Calcified Coromentioning
confidence: 99%
“…In a feasibility trial of 60 patients, the AngioSculpt (Philips, San Diego, CA, USA) balloon showed a high procedural success rate with no serious procedural complications, confirming its technical feasibility and safety when applied to de novo or ISR coronary lesions prior to delivering DES [ 49 ]. Although scoring balloons were not initially intended for severe coronary calcification, preliminary experience has revealed their practicability for use during PCI [ 50 , 51 , 52 ]. In one study, scoring BA led to successful calcium modification of severely calcified lesions in 68%, although there was no control group in this study [ 53 ].…”
Section: Modalities For Coronary Calcium Modificationmentioning
confidence: 99%
“…This postulated "creep phenomenon" is thought to be due to longitudinal forces that occur in the vessel wall under a prolonged sustained load. 13 The Non Slip Elements (NSE) alpha (B Braun, Melsungen, Germany) (previously known as Lacrosse NSE), is a balloon with three nylon scoring elements with a triangular cross section that are embedded in the balloon folds to create a smaller crossing profile. The balloon can be delivered using the "leopard-crawl" technique, creating a wedge into the calcified plaque with a low pressure inflation, then creeping forward during balloon deflation, allowing delivery across severe lesions.…”
Section: Scoring Balloons (Sb)mentioning
confidence: 99%